Looking Forward to the End. /Ou Topos/: An Approach to the Art of Samuel Beckett - Bureu Ramos, Nela (Miscelánea: A Journal of English and American Studies, 2006)
The way to /ou topos/ is the way of most characters in the plays of Samuel Beckett. However, because they are trapped inside the categories of time and place, they can go no further than stasis, to a waiting in hopelessly hopeful stagnation. Their journey has been a relay race ever since Milton’s angels turned Adam and Eve into homeless victims of memory and desire. They are waiting for someone or something to take over —but what: responsibility? power? control? Is the journey Beckett’s poetic of the desire of humans to communicate? Or is it an existential blueprint for the unanchored self? The eschatological catechism of mortality? The aim of my essay is to analyse this literary journey through the eyes, mouth and guts of several of Beckett’s always signal characters.
Keywords: Utopia; Milton; Journey; Beckett; Stasis; /Ou topos/